Editorial Vol. 12 Issue 2 - Sarah D Asebedo (Journal of Financial Therapy, 2021)
This issue features the award-winning Best Paper from the Financial Therapy Association 2021 Annual Conference amongst other notable papers covering various topics including money and grief, attachment styles, money and sex, money scripts and investment advice, financial biases, and the connection between financial threat and health. Be sure to check out the book review of Silver Spoon Kids: How Successful Parents Raise Responsible Children, and the researcher and practitioner profiles introducing Dr. Derek J. Sensenig and Derek Hagen, respectively. We hope you enjoy this issue!